A Rare Case of Insulinoma in a Patient with Hydrocephalus and COVID-19 - Kandinata, Stefanus G.; Mudjanarko, Sony W. (Gaceta Médica de Caracas, 2023)
Insulinoma is a rare entity, in which neuroglycopenia symptoms of recurrent hypoglycemia are often confused with the neuropsychiatric disorder, especially in a patient with hydrocephalus. Hypoglycemia leads to a proinflammatory and procoagulant state, which may worsen the COVID-19 prognosis. We report a case of a 25-year-old woman with an initial presentation of seizure. No previous medical history and drugs were recorded. Intravenous dextrose is administered as low blood sugar was evident but no marked improvement in consciousness was observed.